2008
DOI: 10.1007/s00062-008-8009-5
|View full text |Cite
|
Sign up to set email alerts
|

Ethics in fMRI Studies*

Abstract: Functional magnetic resonance imaging (fMRI) has surfaced as a powerful method to study brain function in humans. While the involvement of neuroradiologists in fMRI studies in the clinical setting is obvious, in neuroscience research most of the investigators are not specialists trained in reading brain images. Advances in neuroimaging are increasingly intersecting with issues of ethical, legal, and social interest. Debate on fMRI is starting, mainly under the impetus of a new interdisciplinary field, neuroeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Our empirical, bottom-up analysis revealed not only a constant quantitative increase in the neuroethics literature over the years but also a constant relative size of the different subject categories. Hence, our study confirmed for neuroethics as a whole what has been reported by previous studies with a more limited focus (Seixas and Ayres Basto, 2008; Lombera and Illes, 2009; Garnett et al, 2011; Gooray and Ferguson, 2013). It also shows that most issues now discussed under the label of Neuroethics have indeed gained much more attention since the middle of the 2000s than they have gained in the antecedent decade and that the issues as such are not new and have not changed much over the years.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our empirical, bottom-up analysis revealed not only a constant quantitative increase in the neuroethics literature over the years but also a constant relative size of the different subject categories. Hence, our study confirmed for neuroethics as a whole what has been reported by previous studies with a more limited focus (Seixas and Ayres Basto, 2008; Lombera and Illes, 2009; Garnett et al, 2011; Gooray and Ferguson, 2013). It also shows that most issues now discussed under the label of Neuroethics have indeed gained much more attention since the middle of the 2000s than they have gained in the antecedent decade and that the issues as such are not new and have not changed much over the years.…”
Section: Discussionsupporting
confidence: 91%
“…These investigations will help to highlight the main differences and similarities of neuroethics and adjoining scientific disciplines and contribute to a better understanding of the current state of neuroethics. Previous bibliometric work on this field has drawn on much smaller subsets of literature (Racine, 2010; Gooray and Ferguson, 2013), has addressed only very particular research fields within the much broader spectrum of neuroethics literature (Seixas and Ayres Basto, 2008; Lombera and Illes, 2009; Garnett et al, 2011, 2013; Boelsen, 2016) or has provided structured compilations of neuroethics literature without any quantitative further analysis (Buniak et al, 2014; Darragh et al, 2015). With this paper we offer the first comprehensive empirical analysis of the development and current state of neuroethics.…”
Section: Introductionmentioning
confidence: 99%
“…We took as a starting point Seixas and Basto's (2008) bibliometrics analysis of neuroethics, the only other study of this nature to date [43] . Although Seixas and Basto's (2008) focus was on impact factor and nation of origin, and on issues affecting radiologists [43] , we revisited their coding guide to provide continuity for the present content analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Still, there remains a disjunction. Neuroscientists in our research argued for ‘balanced’ reporting, which to them means adequate attention to opportunities on the one hand, and limitations and caveats on the other (Seixas and Basto 2008 ). However, the emerging RRI community, emphasises consideration of the wider aspects of technology development, such as societal implementation, ethical acceptability and social desirability (see Fig.…”
Section: Introductionmentioning
confidence: 98%